(untitled) (Journal of Parents and Teachers, 2024)
The article discusses the relationship between feelings and emotional intelligence, highlighting how they influence people’s lives. It mentions the importance of learning to manage emotions and how this can affect actions and decisions. In addition, it is suggested that education in emotional intelligence is fundamental for personal and social development.